Kontrola Komisji Skarbu Litewskiego na sejmie z 1778 roku - Filipczak, Witold (Acta Universitatis Lodziensis. Folia Historica, 2000)
The Seym from 1778 was the first one to control the executive powers whose function was redefined as a result of reforms from the years 1764-1776. Excercising control over the Lithuanian Treasury Board was also important for political reasons. The issue at stake was the conflict involving Podskarbi Antoni Tyzenhauz, who was at the same time President of the Board and leader of Lithuanian royalists. This article presents the members of the committee that supervised the Board. Furthermore, it comments on the way the Board was discussed during the sessions held jointly by the Envoys’ Chamber and the Senate (22.10.1778). It was then that the report from the Board’s activities was submitted. The text also focuses on the debate in the course of which the Board’s activities were accepted through the vote (3-5.11.1778); the discussion on the subject took place after the chambers had been separated from one another. The article shows the backstage political intrigues involving King Stanislaw August and Russian ambassador O. Stackelberg. Their result was imposing limitations on Tyzenhauz’s position in the future.